2017
DOI: 10.1155/2017/6512520
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupuncture on Alzheimer’s Disease in Animal‐Based Research

Abstract: Alzheimer's disease (AD) is a chronic neurodegenerative disease characterized by the accumulation of amyloid beta (A ) plaques, neurofibrillary tangles, and severe functional deficits in the brain. The pathogenesis and treatment of AD remain topics of investigation and significant global socioeconomic issues. The effect of complementary medicine has been investigated in managing AD. Acupuncture, a form of therapy practiced for more than 3000 years, has shown positive effects on several neurological disorders i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
(65 reference statements)
0
15
0
Order By: Relevance
“…A functional magnetic resonance imaging study also revealed that multiple brain regions related to cognitive functions, such as memory function, were activated by acupuncture stimulation including HT7 in patients with AD 25) . In addition, stimulation at HT7 improved cognitive function and increased glucose metabolism in the neocortex and hippocampus in a rat model of AD 27) , and acupuncture stimulation at multiple acupoints including HT7 in healthy undergraduate students resulted in the improvement of memory function as well as the reduction of anxiety 7) . It can thus be assumed that, in the present study, memory function was at least maintained and HT7-acupuncture affected the miceʼs feeling of fear.…”
Section: Discussionmentioning
confidence: 97%
“…A functional magnetic resonance imaging study also revealed that multiple brain regions related to cognitive functions, such as memory function, were activated by acupuncture stimulation including HT7 in patients with AD 25) . In addition, stimulation at HT7 improved cognitive function and increased glucose metabolism in the neocortex and hippocampus in a rat model of AD 27) , and acupuncture stimulation at multiple acupoints including HT7 in healthy undergraduate students resulted in the improvement of memory function as well as the reduction of anxiety 7) . It can thus be assumed that, in the present study, memory function was at least maintained and HT7-acupuncture affected the miceʼs feeling of fear.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that acupuncture can yield protective effects on AD via various pathways such as attenuating neuroinflammation, inhibiting Aβ protein deposition and tau hyperphosphorylation, enhancing glucose brain metabolism, reducing oxidative stress and inhibiting neuronal apoptosis [53,54]. However, there has been no investigation on the effects of acupuncture on the dendritic spines and microtubules in AD-like pathological rodents, especially in aging animals.…”
Section: Discussionmentioning
confidence: 99%
“…e lack of an effective placebo-or sham-acupuncture control reduces the validity of the results. No meta-analysis was included in that review as well [44]. Our subgroup analysis suggests that the effect of EA seemed slightly better than MA.…”
Section: Comparison With Othermentioning
confidence: 99%
“…Park et al published the first review on the effect of acupuncture on AD in animal-based research in 2017 [44]. According to Park's review, MA and EA appeared to generate similar benefits to AD rodents when targeted the same acupoints [44]. One limitation of Park's review is that it included two studies without any experiment and assessment for animal behaviors.…”
Section: Comparison With Othermentioning
confidence: 99%
See 1 more Smart Citation